Use and management of Mimosa species in the Tehuacán-Cuicatlán Valley, a tropical semi-arid region in Mexico (Fabaceae-Mimosoideae) - Camargo-Ricalde, S L; Dhillion, S S (Revista de Biología Tropical, 2004)
We report on the use of 15 Mimosa species within the Tehucán-Cuicatlán Valley, south-central Mexico. Seven of these species are endemic to Mexico, and four species and one variety are endemic to the Valley. We reviewed historical, ethnobotanical and floristic manuscripts, and conducted field studies. Several herbaria were consulted, as well as the BADEPLAM data base. Field work in the Valley has been done from 1994 to date. Most of the Mimosa species occur in the arid tropical scrub and the tropical deciduous forest, which are considered the most endangered vegetation types of the Valley. Our findings show that Mimosa species are used as fodder (45%), fuel (31%), living fences (14%) and construction material (7%). Only one species is used as medicine. Mimosa species are “multipurpose” shrubs/trees of the agrosilvopastoral system of this region.